Harnessing light-activated gallium porphyrins to combat intracellular Staphylococcus aureus using an in vitro keratinocyte infection model - Klaudia Szymczak; Michał Rychłowski; Lei Zhang; Joanna Nakonieczna (Scientific Reports)
Abstract Staphylococcus aureus (S. aureus) can survive inside nonprofessional phagocytes such as keratinocytes, enabling it to evade antibiotics and cause recurrent infections once treatment stops. New antibacterial strategies to eliminate intracellular, multidrug-resistant bacteria are needed. This study used a keratinocyte model infected with methicillin-resistant S. aureus (MRSA) to test light-activated compounds, specifically heme-mimetic gallium (III) porphyrin (Ga3+CHP) and visible light, known as antimicrobial photodynamic inactivation (aPDI), for eliminating intracellular MRSA. Ga3+CHP was found to accumulate more in infected cells, particularly within lysosomal structures where MRSA resides. Flow cytometry and fluorescence microscopy revealed significant colocalization of MRSA and Ga3+CHP. Under aPDI, MRSA showed reduced adhesion to host cells and a 70% reduction in the GFP signal from intracellular bacteria. Additionally, light-activated Ga3+CHP significantly decreased the number of extracellular bacteria, reducing the potential for further infection. This study is the first to analyze aPDI toxicity in real time within an infection model, demonstrating that this method is neither cytotoxic nor phototoxic.